Incidence of bacteriuria at presentation and resulting from urinary catheterization in feline urethral obstruction. Issue 5 (27th June 2019) - Cooper, Edward S.; Lasley, Emma; Daniels, Joshua B.; Chew, Dennis J.
Abstract: Objective: To determine the incidence of bacteriuria at the time of presentation and as a result of indwelling urethral catheterization in naturally occurring feline urethral obstruction (UO). Design: Prospective observational study. Setting: University teaching hospital. Animals: A population of 34 male cats with UO admitted for standard medical care. Interventions: A presenting urine sample was obtained by cystocentesis (precatheterization). After catheterization (performed under strict aseptic technique), a urine sample was obtained through the urinary catheter every 24 hours, as well as just prior to catheter removal. Urine was applied to culture media within 30 minutes of collection or refrigerated immediately at 4°C for subsequent culture the following morning. Samples positive for growth (defined as > 10 4 colony forming units/mL) had bacterial identification and susceptibility testing performed. Measurements and Main Results: All 34 cats enrolled had initial culture performed. Of these, 1 patient died and 2 were euthanized within 24 hours and therefore subsequent cultures were obtained. The remaining 31 cats had median catheterization time of 42 hours (range 20–110 hours). No urine cultures yielded growth at presentation (0/34). A total of 4 of 31 patients (13%) subsequently had bacterial cultures that yielded growth. In these cases, all yielded growth by the 24‐hour time point, and all had the same organism identified on subsequent cultures. Identified bacteria included Streptococcus spp. (3) and Pasteurella spp. (1). Conclusions: The male cats with UO in this study did not have bacteriuria at the time of presentation. The overall incidence of acquired bacteriuria was found to be 13% and could represent a transient bacterial population or true bacterial urinary tract infection. Based on these findings, empirical administration of antibiotics is not warranted in male cats with UO.